Moderating Effect of Social Uncertainty between Capital Budgeting Practices and Performance - Kengatharan, L. (International Journal of Accounting and Financial Reporting, 2017)
Capital budgeting is crucial in order for companies to sustain themselves, survive and flourish in markets and to increase shareholders‟ wealth. The performance of a firm depends on its effective investment decisions. Investing in the 'right' project has an influence on the success of the firm and its future growth. Even though risk and uncertainty factors carefully considered in investment decision making. Therefore, aim of this study was to evaluate the moderating effect of uncertainty between capital budgeting practices and performance based on Sri Lankan emerging market. The data were garnered from primary data and secondary data sources. The primary data were collected from 186 CFOs working in companies in Sri Lanka using self-administered questionnaires. The questionnaire was piloted with a sample of five CFOs. The secondary data were mainly collected from CSE via the Bloomberg website/annual reports for the 5 years period. In order to evaluate the moderating effect of uncertainty between capital budgeting practices and performance, social uncertainty has been considered in this study. Performance was measured by Tobin_q. Data were analysed using descriptive, inferential and multivariate analysis. Findings of the study revealed that an increased level of social uncertainty weakens the positive relationship between sophisticated capital budgeting practices and Tobin_q. In a similar way, an increased level of social uncertainty weakens the positive relationship between advanced capital budgeting practices and Tobin_q and vice versa. Overall, this study has made contribution as identified the moderating effect of uncertainty between the relationship of capital budgeting practices and performances. In a nutshell, beyond its valuable contribution, this study serves as a springboard for future research in many ways.
Keywords: uncertainty